Visualisasi Wanita dalam Al-Qur’an: Penerapan Pendekatan Interpretasi Teks Nashr Hamid Abu Zayd - Muhammad Furqon; Kerwanto Kerwanto; Muh. Adlan Nawawi (Pusat Riset dan Inovasi Nasional, 2023)
Women are often identified with a beauty, as is the case in the selection of the language style of the Qur'an. The diction used by the Qur'an in visualizing women, starting from their creation, association with an angel, as well as the description of their physical characteristics show how noble and honorable they are. The glory of the woman is a symbol of liberation from dehumanization and discrimination against women in jahiliyah and a form of human equality in the eyes of Allah Swt. The purpose of this study was to determine the concept of text interpretation in comprehensively interpreting women and to know the comparison of the formulation of classical interpretation and modern interpretation of the existence of women in the Qur'an and to know what the formulation of intertextuality of the verses visualizing women. The method in this study uses library research that focuses on library data, which are primary sources to classical commentaries and works of Nasr Hamid Abu Zayd as one of the figures of